Rationalization of Islamic Legal Considerations in Marriage Dispensation: A Lesson from Katingan, Central Kalimantan - Iswantoro, Iswantoro; Tobroni, Faiq (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
This paper finds the importance of paying attention to the psychological readiness of children as consideration in granting a marriage dispensation. Katingan Regency Local Regulation Number 9 of 2018 requires applicants for marital dispensation to check their psychological health. This study investigates how such requirements help judges formulate rational legal considerations in handling applications for a marriage dispensation. This study uses qualitative methods and analysis of the intertextuality of legal texts. Kasongan Religious Court Decision Number 39/Pdt.P/2022/PA.Ksn has taken advantage of the implementation of this provision. The judge rejected the application for a marriage dispensation because the results of the hospital's assessment showed that the prospective bride and groom were not psychologically prepared. This decision ruled out the reasons for the applicants on the pretext of only avoiding adultery. The legal considerations refer to the essential objective of Islamic law: the best benefit (maslahat) for children.